Amorphous polyalphaolefins and their use in hot melt compositions with improved sprayability
By developing characteristic amorphous polyα-olefins, the problems of poor high-temperature spraying effect, high resin content and large odor in the existing technology are solved, and high efficient spraying and good stability are achieved at low temperatures, suitable for low temperatures. The application of adhesive is melted to improve process stability and peel value.
Patent Information
- Application Number
- CN201980058095.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-06
- Filing Date
- 2019-09-03
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2039-09-03
AI Technical Summary
When used at high temperatures, the existing amorphous polyα-olefins have problems such as poor spraying effect, high resin content, large odor and high use temperature, making it difficult to achieve uniform spraying at a temperature below 130°C.
A characteristic amorphous polyα-olefin with a viscosity of less than 5000 mPa*s at 190°C, a molar mass distribution of 3 to 8, and a Mz/Mw not exceeding 3.0, produced by free radical or peroxide degradation method , suitable for low temperature melt application of adhesive, reduce spraying temperature to 100°C-140°C, and reduce resin formulations and odor.
Available adhesive with excellent spraying effect at low temperatures, reducing energy consumption and substrate stress, improving process stability and peeling value, reducing "angel hair" phenomenon, and is suitable for bonding with high polymer content agent composition.
Smart Images

Figure SMS_1 
Figure SMS_9 
Figure SMS_10
Abstract
Description
[0001] The present invention relates to an amorphous polyalphaolefin having a viscosity at 190° C. of less than 5000 mPa*s, a molar mass distribution (Mw / Mn) of 3 to 8, a quotient of Mz / Mw of not more than 3.0 and a quotient of Mz / Mn of less than 21.0; the present invention also relates to a process for producing degraded amorphous polyalphaolefins, in particular amorphous polyalphaolefins according to the invention, and to the use of amorphous polyalphaolefins according to the invention or produced according to the invention in melt-applied adhesive compositions.
[0002] In the application of hot-melt adhesives, nozzles (spiral nozzles, signature nozzles, etc.) are used in many cases, in which the hot-melt formulation is sprayed in melt form through the nozzle under the effect of pressure onto the substrate.
[0003] The problem with formulations containing amorphous polyalphaolefins (hereinafter referred to as APAO) is that they have a higher use temperature and a lower quality spray effect compared to formulations based on SBS / SIS [styrene-butadiene-styrene block copolymers and styrene-isoprene-styrene block copolymers]. In particular, systems based on SBS / SIS are applied at a temperature of about 120°C and provide a very uniform spray effect. The disadvantage of this system is that the formulation contains a high content of resin system (usually more than 40% by weight) and the styrene-based raw materials produce an unpleasant odor. APAO-based systems have a clear advantage in this regard, they must be formulated with significantly less resin (less than 30% by weight of resin) and also have less odor.
[0004] However, a serious disadvantage is the significantly higher application temperatures compared to SBS / SIS systems of above 140° C. For example, EP 1 442 089 B1 describes the application of APAO and syndiotactic PP at more than 170° C. using a spiral nozzle.
[0005] For example, US Pat. No. 8,921,474 B2 describes the generally poor sprayability of hot melt adhesives based on APAO, which is why systems based on SBS or rubber are used.
[0006] EP 0 442 045 B1 describes the use of hot melt adhesive formulations at <200° C.
[0007] EP 1124911 B1 describes an APAO system which is preferably sprayable at 140-160° C., but with the addition of 5% to 30% oil. US 20160222258 A1 proposes an APAO system with SBS in order to reduce the processing temperature.
[0008] From an application perspective, a recurring requirement is an operating temperature of <130°C when using the signature nozzle. To date, the APAO system has not been able to achieve these goals.
[0009] The problem addressed by the present invention is therefore that of providing one or more APAOs or melt-applied adhesive compositions based on said APAOs which do not have one or more disadvantages of the prior art.
[0010] It has surprisingly been discovered that amorphous polyalphaolefins meeting certain parameters can solve one or more of the above-mentioned problems.
[0011] The present invention therefore provides an amorphous polyalphaolefin as described below, characterized in that the viscosity at 190° C. is less than 5000 mPas, the molar mass distribution (Mw / Mn) is 3 to 8, the quotient Mz / Mw does not exceed 3.0, and the quotient Mz / Mn is less than 21.0.
[0012] The invention also provides a method for producing degraded amorphous polyalpha-olefins, characterized in that the amorphous polyalpha-olefins are obtained by free radical degradation, preferably peroxide degradation, of amorphous polyalpha-olefins, the viscosity of the amorphous polyalpha-olefins at 190° C. not exceeding 5000 mPas, the degradation reaction being carried out within a period of 15 seconds to 1200 seconds. Methods for degrading polymers are known in principle. US 4,707,524 A describes the degradation of polypropylene, for example, by mixing with peroxides. US 3,121,070 A describes the degradation of polypropylene at temperatures of 275-450° C. US 3,940,379 A describes the degradation of polypropylene in the presence of oxygen or peroxides to obtain polypropylene with a higher melt flow rate. Markus Gahleitner gives an overview of the melt rheology of polyolefins in Prog. Polym. Sci. 26 (2001) 895-944.
[0013] The invention also provides for the use of an APAO according to the invention or an APAO produced according to the invention in a melt-applied adhesive composition.
[0014] Using APAO according to the present invention in melt-applied adhesive compositions can reduce the spraying temperature to 100°C-140°C.
[0015] As a result, this material has less tendency to crack (break or split of the polymer).
[0016] The APAO according to the present invention can be used at 120°C with the same formulation as before (without SBS / SIS or even without oil), with low use temperature, lower resin formulation, less unpleasant odor, and excellent spraying effect, which was not possible before.
[0017] Due to the lower spraying temperature, less energy is required to melt the molten applied adhesive composition. In addition, due to the lower temperature, the stress on the substrate is also less, or a less thermally stable substrate material can be used.
[0018] The spraying effect of the melt-applied adhesive composition used according to the invention is more uniform, which is related to the fact that the material can be applied more uniformly. This leads to significantly better peel values, i.e. the ease of separation from the nonwoven substrate. Here, the peel values obtained in the 25 mm tape are greater than 2.2 N, while previously the peel values were below 2.0 N (determined in each case according to ASTM D1876).
[0019] Another advantage is greater process stability. Avoiding the creation of "angel hair" (hot melt strands ejected from the nozzle in a non-directional manner) extends cleaning cycles and reduces cleaning complexity, ultimately leading to longer run times.
[0020] The melt-applied adhesive composition based on APAO according to the invention can be used not only in the nozzle process but also in other processes, for example those in which a slot die is used.
[0021] Melt-applied adhesive compositions based on the APAO according to the invention or produced according to the invention can be formulated with much higher polymer contents compared to formulations based on metallocene-based systems, thereby significantly reducing the complexity of the formulation. Thus, melt-applied adhesive compositions based on the APAO according to the invention or produced according to the invention can be formulated with up to 70% by weight or even more than 95% by weight of polymer (APAO), whereas in metallocene-based systems, typically only a maximum of 40% by weight of polymer (polyolefin) based on the weight of the entire formulation may be used.
[0022] The APAO according to the invention, the method according to the invention and the inventive use of the APAO are described below by way of example, without any intention to limit the invention to these illustrative embodiments. When ranges, general formulae or classes of compounds are specified below, they should not only cover the corresponding ranges or groups of compounds explicitly mentioned, but also all sub-ranges and sub-groups of compounds that can be obtained by omitting individual values (ranges) or individual compounds. When references are made to documents in the context of this specification, their contents should fully constitute part of the disclosure of the present invention, especially with regard to the matters involved. When numbers are expressed as percentages, these numbers are expressed as weight percentages unless otherwise stated. When average values, such as molar mass average values, are specified below, they are numerical average values unless otherwise stated. When the properties of materials are specified below, such as viscosity, etc., these properties are the properties of the material at 25°C unless otherwise stated. When chemical (empirical) formulas are used in the present invention, the specified coefficients can be not only absolute numbers, but also average values. The coefficients relating to polymeric compounds are preferably average values.
[0023] The amorphous polyalphaolefin according to the invention is characterized in that its viscosity at 190° C. is less than 5000 mPas, preferably 1000-4000 mPas, the molecular weight distribution (Mw / Mn) is from 3 to 8, preferably from 4 to 7, the quotient of Mz / Mw is less than 3.5, preferably from 1.1 to 2.9, and the quotient of Mz / Mn is less than 21.0, preferably from 1.1 to 19.9.
[0024] Mw is the weight average molecular weight, Mn is the number average molecular weight, and Mz is the centrifugal average molecular weight. The molecular weights Mw, Mn and Mz are determined by HT-GPC [high temperature gel permeation chromatography] as described in DIN 55 672. Specifically, analytical HT-GPC was performed at 150°C using a PL220 oven (Agilent, Waldbronn) with an integrated isocratic pump. The mobile phase used was 1,2,4-trichlorobenzene (TCB) (Merck, Darmstadt) doped with about 1 g / L of butylated hydroxytoluene (BHT) at a flow rate of 1 ml / min, and the stationary phase used was an Agilent PLgel Olexis Guard (50 x 7.5 mm, precolumn) and three Agilent PLgelOlexis (300 x 7.5 mm). Detection was performed by an IR detector (type IR4, PolymerChar, Valencia, Spain). The data sets were evaluated by WinGPC software (Polymer Standards Service, Mainz) using polystyrene calibrants (EasiCal PS-1, Agilent).
[0025] The viscosity is determined analogously to DIN 53 019 by measurement with a rotational viscometer at 190° C. The viscosity is determined by measurement using a CAP 2000+ cone and plate viscometer from Brookfield at 190° C. with a viscosity dependence shear rate analogous to the following table:
[0026]
[0027] The calibration of the Brookfield viscometer was done using a Newtonian standard sample type 500000BW from Zentrum für Messen and Kalibrieren & Analytik GMBH with the corresponding calibration certificate.
[0028] The APAO is preferably an APAO rich in propylene or 1-butene. Based on all monomers, the preferred APAO rich in propylene is preferably based on propylene greater than 50% by weight, preferably 51-98% by weight as a monomer. In addition, the APAO rich in propylene may include 1-butene and / or ethylene, preferably 1-butene and ethylene as comonomers. Based on all monomers, the total amount of 1-butene and ethylene here is less than 49% by weight, preferably 0-25% by weight, preferably 1-15% by weight. Based on all monomers, the preferred APAO rich in 1-butene is preferably based on 1-butene greater than 50% by weight, preferably 51-98% by weight as a monomer. In addition, the APAO rich in 1-butene may include propylene and / or ethylene, preferably propylene and ethylene as comonomers. Based on all monomers, the total amount of propylene and ethylene here is less than 49% by weight, preferably 0-25% by weight, preferably 1-15% by weight.
[0029] The amorphous polyalphaolefin according to the invention may advantageously comprise 0.01% to 3% by weight of at least one antioxidant. The antioxidant used may be any substance known as an antioxidant and / or inhibitor, i.e. a substance that prevents the propagation of free radical reactions. The amorphous polyalphaolefin according to the invention preferably contains a sterically hindered amine, such as a piperidine derivative, preferably a sterically hindered phenol, such as Irganox 1010, Naugard XL1, Songnox 1035. In this way, the degradation of APAO and / or the yellowing of APAO can be prevented or reduced.
[0030] The APAO according to the invention preferably comprises 0.01 wt. % to 3 wt. % of at least one degradation product of a free radical former. Preferably, the APAO according to the invention comprises benzoic acid, methanol, butanol, tert-butanol, propionic acid and / or 2,5-dimethylhexan-2,5-ol as degradation products of a free radical former.
[0031] The APAO of the present invention can be prepared by the method of the present invention as described below.
[0032] The process according to the invention for producing degraded amorphous polyalpha-olefins is characterized in that the amorphous polyalpha-olefin having a viscosity of not less than 5000 mPas, preferably 6000-100 000 mPas, and more preferably 7500-75 000 mPas at 190° C. is subjected to free radical degradation, preferably peroxide degradation, and the degradation reaction is carried out within a time of 15 to 1200 seconds. The free radical, preferably peroxide degradation is preferably carried out in a mixing device, preferably in an extruder.
[0033] The APAO used is preferably an APAO rich in propylene or 1-butene. Based on all monomers, the preferred APAO rich in propylene is preferably based on propylene as a monomer greater than 50% by weight, preferably 51-98% by weight. In addition, the APAO rich in propylene may include 1-butene and / or ethylene, preferably 1-butene and ethylene as comonomers. Based on all monomers, 1-butene and ethylene here total less than 49% by weight, preferably ethylene content of 0-25% by weight, preferably 1-15% by weight. Based on all monomers, the preferred APAO rich in 1-butene is preferably based on 1-butene as a monomer greater than 50% by weight, preferably 51-98% by weight. In addition, the APAO rich in 1-butene may include propylene and / or ethylene, preferably propylene and ethylene as comonomers.
[0034] Propylene and ethylene here total less than 49% by weight, based on all monomers, preferably the ethylene content is from 0 to 25% by weight, preferably from 1 to 15% by weight.
[0035] Preferably, the free radical degradation is carried out in the presence of a free radical former, which is preferably selected from dibenzoyl peroxide, tert-butyl peroxyisopropyl carbonate, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butyl peroxide and / or preferably p-methane hydroperoxide. The proportion of free radical former used is preferably 0.01% to 10% by weight, preferably 0.1% to 5% by weight, based on the total amount of APAO and free radical former.
[0036] The degradation reaction in the process according to the invention is preferably carried out at a temperature of 100 to 350° C., preferably 150 to 250° C. The degradation is preferably carried out in the melt.
[0037] Depending on the reactivity and concentration of the free radical former used, the degradation reaction preferably takes place within a period of 30 to 600 seconds.
[0038] The degradation reaction is preferably carried out within a time t of 15 to 1200 seconds, preferably 30 to 600 seconds, at a temperature T of 100 to 350° C., preferably 150 to 250° C., wherein the proportion A of the free radical former used, based on the total of APAO and free radical former, is 0.01 to 10% by weight, preferably 0.1 to 5% by weight, with the proviso that the product tx T x A is 500 to 1 000 000 [seconds ° C. weight %], preferably 1000 to 100 000 [seconds ° C. weight %].
[0039] The degradation reaction in the process according to the invention is preferably carried out in a mixing device. The mixing device used is preferably an extruder, a kneader or a pressure reactor equipped with a stirrer. Particularly preferably, the reaction is carried out in an extruder. Particularly preferably, the degradation reaction is carried out in a mixing device, preferably an extruder, using the times, temperatures and proportions of free radical formers specified above as preferred and especially more preferred.
[0040] The process according to the invention is particularly suitable for producing the APAO according to the invention.
[0041] The APAO according to the invention or the APAO produced according to the invention can be used in any hot melt adhesive application in which APAO according to the prior art can also be used.
[0042] More specifically, the APAO according to the invention or the APAO produced according to the invention is used or used as a melt-applied adhesive composition. Preferably, these compositions comprise 50% to 100% by weight, preferably at least 70% by weight and more preferably at least 90% by weight of the APAO according to the invention or the APAO produced according to the invention. Other components of the melt-applied adhesive composition may be, in particular, tackifying resins and / or waxes, in particular Fischer-Tropsch waxes or polyethylene waxes. Preferred melt-applied adhesive compositions comprise 50% to 100% by weight of the APAO according to the invention or the APAO produced according to the invention, 0% to 40% by weight of a tackifying resin, for example hydrogenated C5 / C9 Escorez from Exxon Mobil. TM 5300, and 0% to 10% by weight of a Fischer-Tropsch wax or a PE wax, such as Shell GTL Sarawax SX80.
[0043] The melt-applied adhesive composition can be applied by means of a nozzle, a slot die, a melt-applied glue gun or by melt casting, preferably by means of a nozzle. Particularly suitable coating systems with an application unit for spraying the adhesive are, for example, systems from the company Nordson (hereinafter referred to as Nordson) or ITW Dynatec GmbH (hereinafter referred to as ITW). Suitable nozzles are, for example, the UNIVERSAL TM SIGNATURE TM Nozzle or controlled fiberization nozzle (Controlled Fiberization) or ITW's UFD TM Other possible nozzles are listed in Table A.
[0044] Table A: List of nozzles from Nordson and IWT
[0045] nozzle source Generation rate Recommended adhesive viscosity (190℃) CF (controlled fibrosis) Nordson 10-350m / min 4000-8000mPa*s SUMMIT Nordson 10-400m / min 1500-10000mPa*s Continuous Signature Nordson 10-650m / min 1000-3000mPa*s Intermittent Signature Nordson 10-650m / min 1000-6000mPa*s Control Coat Nordson 10-600m / min 1000-3000mPa*s UFD RF ITW Up to 500m / min Up to 6000mPa*s UFD Omega ITW Up to 500m / min Up to 6000mPa*s UFD HS RF ITW Up to 650m / min 1000 to 6000 mPa*s UFD HS Omega ITW Up to 650m / min 1000 to 6000 mPa*s UFD SCS ITW Up to 650m / min 1000 to 15000 mPa*s
[0046] According to the invention, the melt-applied adhesive composition can be used in the following applications: packaging, preferably cardboard packaging or paper, construction, especially timber construction, carpets, woodworking, preferably profile sealing and edge gluing, automotive, preferably vehicle roofs, air filters or vehicle lights, mattresses, asphalt, hygiene products, preferably diapers or sanitary napkins.
[0047] As well as conventional hot melt applications, the APAO according to the invention or the APAO produced according to the invention can also be used as an additive for other non-polar plastics such as polypropylene, polyethylene and polybutylene.
[0048] These may be suitable as compatibilizers or as carrier matrices for masterbatch applications in order to incorporate other additives such as pigments or fibers.
[0049] Even without further elaboration, it is assumed that a person skilled in the art can utilize the above description to the fullest extent possible.Therefore, the preferred embodiments and examples should be interpreted as merely descriptive disclosures and not limiting in any way.
[0050] Figure 1 FIG. 3 further illustrates the subject matter of the present invention, but the subject matter of the present invention is not intended to be limited thereto.
[0051] Figure 1is a schematic diagram of an apparatus with which the degraded APAO used according to the invention can be produced. The apparatus has at least one mixing apparatus M, a feed R for a pre-radical former, a feed A for the APAO to be degraded, and optionally a device for applying a vacuum V. The product that leaves the mixing apparatus M as a product is a degraded APAO by-product (APAO Ad).
[0052] Figure 2a An example of a good spray pattern is shown. Clearly the pattern is regular and the wire does not have any holes or drips.
[0053] Figure 2b An example of a bad spray pattern is shown. It is clear that the pattern is irregular and the wire has holes or drops.
[0054] Figure 3a The spraying onto the roller is depicted. From this perspective, it is easy to determine that the spray wire is deflected in the coating direction and in the direction opposite to the coating direction.
[0055] Figure 3b is a schematic diagram of spraying adhesive from nozzle D onto nonwoven fabric V1. AR represents the application direction or the advancing direction of nonwoven fabric V1.
[0056] A further nonwoven V2 is applied to the applied adhesive.
[0057] Figure 4a Depicted is a spray template used to quantify deflection, onto which the application has been made. The template is a coated and reverse laminated substrate (polypropylene / polypropylene). Deflections of 0 cm, 0.5 cm, 1 cm, 2 cm, and 3 cm correspond to 0, 0.5, 1, 2, and >2 categories.
[0058] Figure 4b is a schematic diagram of the spray template used to quantify the skew.
[0059] The subject matter of the invention is explained in detail in the following examples without intending to restrict the subject matter of the invention thereto. Example:
[0060] Example 1: Production of degraded APAO in a stirred reactor
[0061] 400 g of Evonik Resource Efficiency GmbH 750 was introduced into a laboratory pressure reactor with a stirrer and heated to 170° C. Once this temperature was reached, 4% by weight (16 g) of peroxide (Peroxan HX [2,5-dimethyl-2,5-di(tert-butylperoxy)hexane] from Pergan GmbH) was added and the mixture was stirred for 5 minutes. Subsequently, the mixture was discharged and the melt viscosity was determined on a Brookfield laboratory viscometer at 190° C. (determination method, see above). The viscosity of the mixture discharged at 190° C. was 4000 mPa*s. Using The viscosity of the 750 was measured at 190°C and the obtained value was about 50 000 mPa*s. GPC analysis gave the following values: Mz: 145100 [g / mol]; Mw: 60390 [g / mol]; Mn: 14180 [g / mol]; Mw / Mn: 4.3; Mz / Mw: 2.4; Mz / Mn: 10.2.
[0062] In the same manner, low viscosity base polymer B1 ( EP V2094, non-conforming product, viscosity = 7700 mPa*s at 190°C) was subjected to a first degradation experiment. Table B shows the experimental parameters used and the properties measured. 408 (indicated as B2 in the table) and The performance of 750 (denoted as B3 in the table) is compared.
[0063] Table B: Products, experimental parameters and product properties used in Example 1 determined
[0064] Base polymer B1 B1 B1 B1 B1 B2 B3 Viscosity [mPa*s] 7700 5302 3636 4500 2761 8200 52500 Peroxide [wt%] 0 0.5 1.5 0.5 1.5 0 0 Temperature [℃] 0 130 130 170 170 0 0 Mn 12700 10950 11350 10480 8350 12000 17890 M 74950 75800 69900 65450 57250 82800 149810 Mz 275500 312500 249500 198000 151500 388000 564600 Mw / Mn 5.9 6.9 6.2 6.2 6.9 6.9 8.4 Mz / Mw 3.7 4.1 3.6 3.0 2.6 4.7 3.8 Mz / Mn 21.7 28.5 22.0 18.9 18.1 32.3 31.6
[0065] As can be seen from Table B, APAO having the desired material / product properties can be obtained by free radical degradation of amorphous polyalphaolefins having a viscosity of not less than 5000 mPa*s at 190°C.
[0066] Example 2: Pilot scale production of degraded APAO in an extruder
[0067] 20 kg of granular 750 initial materials were fed into the Bersdorf DSK42 extruder via the feed. At the same time, 1.8 kg / h of 750 and about 200 g / h of 50 wt. % Peroxan PK295V [1,1-di-(tert-butylperoxy)-3,3,5-trimethylcyclohexane] (mixture in isododecane) from Pergan GmbH. The residence time (reaction time) of the reaction mixture in the extruder was 30 seconds and the temperature in the extruder was 160° C. The viscosity of the mixture discharged at 190° C. was 2800 mPa*s. Mz: 149200 [g / mol]; Mw: 61110 [g / mol]; Mn: 14350 [g / mol]; Mw / Mn: 4.3; Mz / Mw: 2.4; Mz / Mn: 10.4.
[0068] Example 3: Production of melt-applied adhesive composition
[0069] The polymer obtained in Example 2 was processed to give a melt-applied adhesive composition. For this purpose, the components specified in Table C below were mixed with one another at 190° C. by stirring.
[0070] Table C: Components used for producing melt-applied adhesive compositions and their mass percentages (%) in brackets
[0071] Example APAO Tackifying resin wax 3a From Example 2 (65) <![CDATA[Escorez TM 5380(30)]]> Sarawax SX80(5) 3b From Example 2 (100) 3c From Example 2 (70) <![CDATA[Escorez TM 5300(30)]]>
[0072] Example 4: Sprayability Verification
[0073] In order to verify the sprayability, a test series of 14 experiments was carried out for each melt-applied adhesive formulation at three temperatures (120°C, 140°C and 160°C). At the same time, parameters such as the air pressure at the nozzle and the mass of the melt-applied adhesive applied were changed, taking into account the application window of the nozzle used. The experiment was carried out using a Nordson Meltex hot melt applicator spray system (product model: MX 3012-1 / 0220-2086). The nozzle used was a Nordson low-flow Signature nozzle. The hot melt formulation to be sprayed was melted at 190°C in a tank and delivered to the nozzle by a pump, where the applied airflow was used to deposit the hot melt formulation on the non-woven substrate passing under the nozzle by the heated airflow at the nozzle outlet. Each experiment was recorded for 10 seconds. See Table 1 for different experimental parameters.
[0074] Mass of melt-applied adhesive applied: 0.5-10 g / m 2 [Depending on pump speed and belt speed]
[0075] Substrate speed: 15m / min
[0076] Pressure / air rate at nozzle: 10-130l(STP) / min / 1-4 bar per nozzle
[0077] Table 1: Experimental parameters used
[0078]
[0079] Evaluation of spray pattern
[0080] The spray pattern was evaluated using the following criteria. The evaluation results are recorded in Tables 2a to 2c.
[0081] Visual impression of the spray pattern:
[0082] The visual impression of the spray pattern will be assessed. This is a subjective assessment.
[0083] In the case of a good spray pattern, the molten applied adhesive forms lines that cover the area just below the nozzle. No lines extend to the left or right, and the surface is covered in a regular pattern. Figure 2a An example of a good spray pattern is shown.
[0084] In case of a poor spray pattern, the melt-applied adhesive is applied to the substrate in the form of thick lines and / or dots. The lines are wider than the nozzle and irregular. There may be large holes in the spray pattern, and some parts of the substrate may not be covered by the melt-applied adhesive. Figure 2b An example of a poor spray pattern is shown.
[0085] Evaluate:
[0086] 0 = Good spray pattern
[0087] 1 = Poor spray pattern
[0088] Edge stability
[0089] Edge stability is related to the stability of the line. Many holes in the line indicate poor edge stability of the spray pattern. Ignore individual outliers.
[0090] Evaluate:
[0091] 0 = Edge stability
[0092] 1 = Edge instability
[0093] Deflection of wire (from stencil mask):
[0094] The skew relates to areas of the spray pattern where the lines lie outside the 2.5 cm center mark (skew is determined only for lines visible against a dark template mask).
[0095] Evaluate:
[0096] 0 = no skew
[0097] 0.5 = Deflection length up to 0.5 cm
[0098] 1 = Deflection length up to 1 cm
[0099] 2 = Deflection length up to 2 cm
[0100] 3 = Deflection greater than 2 cm in length
[0101] Filament:
[0102] The skew was related to areas of the spray pattern where very thin filaments were located outside the 2.5 cm center mark (the filaments were barely visible against the dark stencil mask and could only be seen by holding the stencil mask up to a light).
[0103] Evaluate:
[0104] 0 = no skew
[0105] 0.5 = Deflection length up to 0.5 cm
[0106] 1 = Deflection length up to 1 cm
[0107] 2 = Deflection length up to 2 cm
[0108] 3 = Deflection greater than 2 cm in length
[0109] Evaluation of spraying videos
[0110] Apply just below the nozzle:
[0111] The melt applied adhesive will be applied just below the nozzle. Any deviation to the left or right is undesirable. A stencil mask is used for evaluation.
[0112] Evaluate:
[0113] 0 = The melt-applied adhesive was applied in a straight line directly below the nozzle with a maximum deflection of 0.5 cm.
[0114] 1 = The filaments of the melt-applied adhesive do not even reach the substrate because they deflect too significantly, or the filaments of the melt-applied adhesive deflect to such an extent that they do not reach the substrate in a straight line, or deflect by more than 0.5 cm.
[0115] Filaments deflect from the stencil mask or form "angel hair":
[0116] In this case, only a spray width of 2.5 cm is considered, and the spray filaments are deflected in the direction of application or opposite to the direction of application. If more than 2.5 cm is applied, or the filaments fly over the substrate without reaching it, it is called "angel hair".
[0117] Evaluate:
[0118] 0 = No deflected wire
[0119] 0.5 = Wire with a deflection of up to 0.5 cm
[0120] 1 = Wire deflection up to 1 cm
[0121] 2 = Wire deflection up to 2 cm
[0122] 3 = Wire deflection up to 3 cm
[0123] 4 = Wire with a deflection greater than 3 cm
[0124] Spraying onto a roller is depicted in Figure 3. From this perspective, it is easy to determine that the spray wire is deflected in the coating direction and in the direction opposite to the coating direction.
[0125] score:
[0126] The score indicates the total score. The smaller the number, the better the sprayability.
[0127] Sprayability:
[0128] The lower the total score obtained in the evaluation, the better the sprayability of the melt-applied adhesive examined. A score of 0 indicates a sprayability of 100% and a score of 11 indicates a sprayability of 0%.
[0129] Tables 2a to 2c show by way of example the evaluation of 14 spray tests at 140° C. using a melt-applied adhesive composition according to Example 3a. Table 3 shows the sprayability in % of all tested melt-applied adhesive compositions.
[0130] Table 2a: Parameters and results of the evaluation of Experiments 1 to 5
[0131]
[0132] Table 2b: Evaluation parameters and results of Experiments 6 to 10
[0133]
[0134] Table 2c: Parameters and results of the evaluation of Experiments 11 to 14
[0135]
[0136] Spr.: sprayability
[0137] Table 3 shows the sprayability in % for all melt-applied adhesive compositions tested.
[0138] Preparation temperature Sprayability 3a 140℃ 84.7% 3a 160℃ 82.8% 3b 140℃ 87.3% 3b 160℃ 77.9% 3c 140℃ 81.5% 3c 160℃ 88.6%
[0139] As can be inferred from Table 3, the sprayability of adhesives and / or polymers can be evaluated using a detailed breakdown of the individual evaluation criteria. Based on this approach, it can be demonstrated that the sprayability of degraded polymers is significantly improved and that, for example, changes in gas pressure, temperature and the amount of sprayed polymers in g / min or g / m 2 A larger application range related to the unit application amount.
Claims
1. Degraded amorphous poly-alpha-olefin, characterized in that The viscosity at 190° C. is less than 5000 mPas, the molecular weight distribution (Mw / Mn) is 3 to 8, the quotient of Mz / Mw does not exceed 3.0, the quotient of Mz / Mn is less than 21.0, Mw, Mn and Mz are determined by high temperature gel permeation chromatography, and the viscosity is determined by a rotational viscometer, wherein the amorphous polyalpha-olefin is a propylene- or 1-butene-rich amorphous polyalpha-olefin, the propylene-rich amorphous polyalpha-olefin is based on propylene as a monomer to a degree of greater than 50% by weight based on all monomers, and furthermore, the propylene-rich amorphous polyalpha-olefin comprises 1-butene and ethylene as comonomers, the 1-butene-rich amorphous polyalpha-olefin is based on 1-butene as a monomer to a degree of greater than 50% by weight based on all monomers, and furthermore, the 1-butene-rich amorphous polyalpha-olefin comprises propylene and ethylene as comonomers, the amorphous polyalpha-olefin comprises 0.01% to 3% by weight of at least one degradation product of a free radical initiator.
2. The amorphous poly-α-olefin according to claim 1, characterized in that The viscosity at 190°C is 1000-4000 mPas.
3. The amorphous poly-α-olefin according to claim 1, characterized in that The quotient of the molecular weight distribution Mz / Mw is from 1.1 to 2.
9.
4. The amorphous poly-α-olefin according to claim 1, characterized in that The quotient of Mz / Mn is 9.1 to 19.
9.
5. The amorphous poly-α-olefin according to claim 1, characterized in that include 0.01 wt. % to 3 wt. % of at least one antioxidant.
6. A method for producing degraded amorphous poly-alpha-olefins, characterized in that The amorphous poly-α-olefin is subjected to free radical degradation, wherein the free radical degradation is carried out in the presence of a free radical former, the proportion of the free radical former used is 0.01 wt % to 10 wt % based on the sum of the amorphous poly-α-olefin and the free radical former, the degradation reaction is carried out at a temperature of 150-350° C., the viscosity of the amorphous poly-α-olefin at 190° C. is not less than 5000 mPas, and the degradation reaction is carried out within a time of 15 seconds to 1200 seconds, wherein the amorphous poly-α-olefin is rich in Amorphous polyalpha-olefin containing propylene or 1-butene, the propylene-rich amorphous polyalpha-olefin is based on propylene as a monomer to a degree of greater than 50% by weight based on all monomers, and furthermore, the propylene-rich amorphous polyalpha-olefin comprises 1-butene and ethylene as comonomers, the 1-butene-rich amorphous polyalpha-olefin is based on 1-butene as a monomer to a degree of greater than 50% by weight based on all monomers, and furthermore, the 1-butene-rich amorphous polyalpha-olefin comprises propylene and ethylene as comonomers.
7. The method of claim 6, wherein the free radical degradation is peroxide degradation.
8. The method according to claim 6, wherein the viscosity of the amorphous poly-α-olefin at 190°C is 6000-100000 mPas.
9. The method according to claim 6, wherein the viscosity of the amorphous poly-α-olefin at 190°C is 7500-75000 mPas.
10. The method according to claim 6, characterized in that The free radical degradation is carried out in an extruder.
11. The method according to claim 6, wherein: The free radical former is selected from dibenzoyl peroxide, tert-butyl peroxyisopropyl carbonate, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, di-tert-butyl peroxide or p-methane hydroperoxide.
12. The method according to claim 6, characterized in that The free radical formers are used in a proportion of 0.1% to 5% by weight.
13. The method according to claim 6, characterized in that The degradation reaction is carried out at a temperature of 150-250°C.
14. The method according to any one of claims 6 to 13, characterized in that The degradation reaction is carried out within a time period of 30 seconds to 600 seconds.
15. The method according to any one of claims 6 to 13, characterized in that The degradation reaction is carried out within a time t of 15 to 1200 seconds at a temperature T of 100 to 350° C., wherein the proportion A of the free radical former used is 0.01 to 10% by weight, based on the sum of the amorphous polyα-olefin and the free radical former, with the proviso that the product tx Tx A is 500 to 1 000 000 [seconds° C. weight %].
16. The method according to claim 15, wherein: The time t is 30 seconds to 600 seconds.
17. The method according to claim 15, wherein: The temperature T is 150-250°C.
18. The method according to claim 15, wherein: The proportion A of the free radical former is 0.1-5% by weight.
19. The method according to claim 15, wherein: The product of tx T x A is 1000-100 000 [sec °C wt %].
20. The method according to any one of claims 6 to 13, 16 to 19, characterized in that The reaction is carried out in a mixing unit.
21. The method according to claim 20, characterized in that The reaction is carried out in an extruder.
22. The method according to any one of claims 6 to 13, 16 to 19, 21, characterized in that Preparation of the amorphous poly-alpha-olefin according to any one of claims 1 to 5.
23. Use of the amorphous polyalphaolefin according to any one of claims 1 to 5 or produced by the process according to any one of claims 6 to 22 in a melt-applied adhesive composition.
24. The use according to claim 23, characterized in that The composition comprises at least 70 wt% of the amorphous polyalphaolefin according to any one of claims 1 to 5 or an amorphous polyalphaolefin prepared by the method according to any one of claims 6 to 22.
25. The use according to claim 24, characterized in that The composition comprises at least 90 wt% of the amorphous polyalphaolefin according to any one of claims 1 to 5 or an amorphous polyalphaolefin prepared by the method according to any one of claims 6 to 22.
26. The use according to claim 23 or 24, characterized in that The melt-applied adhesive composition is applied through a nozzle, a slot die, a melt-applied glue gun, or by melt casting.
27. The use according to claim 26, characterized in that The melt-applied adhesive composition is applied by means of a nozzle.
28. The use according to claim 26, characterized in that The melt-applied adhesive composition is applied by means of a spiral nozzle.
29. The use according to any one of claims 23 to 25, 27 and 28, characterized in that The melt-applied adhesive composition is used in the following applications: packaging, construction, carpet, woodworking, automotive, mattresses, asphalt, hygiene.
30. Use according to claim 29, wherein the packaging is a cardboard packaging or paper.
31. The use according to claim 29, wherein the building is a timber structure building.
32. The use according to claim 29, characterized in that The melt-applied adhesive composition is used in the following applications: profile sealing and edge gluing.
33. The use according to claim 29, characterized in that The melt-applied adhesive composition is used in the following applications: vehicle roofs, air filters or automotive lamps.
34. The use according to claim 29, wherein the sanitary product is a diaper or a sanitary napkin.
Citation Information
Patent Citations
Tailored rheology hotmelt spray composition
EP0442045B1
Sprayable hot-melt adhesive
EP1124911B1
Hot melt adhesive composition based on a blend of amorphous poly-alpha-olefin and syndiotactic polypropylene
EP1442089B1
Performance APAO hot melt adhesives containing high melt flow rate hydrogenated styrene block copolymers
US20160222258A1
Thermally modified polymers of polypropylene and other polymers and process for preparing the same
US3121070A